(3bUjOI aj eOM CHj GdfUQ eMeO Hf efUhQ Hf eMeO YejO Gdedc GdcfOjs - (3eMeO HQgGfj Ydjs
(3ChdgG (B:s
(3CcPi jMGPj hO cd bQjf (B*** (3Ce gPg Tje GdXHGA GdYjf , bUhG Ydi MOjK ef bJd Gdghi (B*** (3Cf GdJBSj QhM cd MRjfs
(3BNQgG (B:s
(3cGdSja Qhfb CKQg aj eJfg (B*** (3heVGDg aj LOg GdeSfhf , TgOJ YdGg Cf YfUQ PGJg (B*** (3eSc hYfUQ ZjQg ef Wjfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdCOHs